Pengaruh Pertumbuhan Ekonomi, Upah Minimum Dan Tingkat Pengangguran Terhadap KemiskinanDi Kabupaten Bolaang Mongondow - Indra Mario Saul; Daisy S. M. Engka; Steeva Y. L. Tumangkeng (Jurnal Riset Multidisiplin Edukasi, 2025)
This study attempts to examine the impact of economic growth, minimum wage and unemployment bolaang mongondow to poverty in the district.The analysis used is multiple linear regression, using data time series poverty, economic growth, minimum wage, and unemployment rate from year 2013-2023.And the research suggests that on this fact does not affect economic growth significantly to poverty, minimum wage did not influence significantly to poverty and unemployment significant impact on poverty in kabupaten bolaang mongondow.And together economic growth, minimum wage, to poverty and unemployment in the bolaang mongondow